Legal Protection of Architectural Works as Copyright: An Epistemological and Islamic Law Perspective - Ruhtiani, Maya; Prihatinah, Tri Lisiani; Sulistyandari, Sulistyandari; Park, Hyun Kyung; Whindari, Yayuk (El-Mashlahah, 2024)
The research examined the problem of the legal protection of architectural works as copyright. It described the concept of the legal protection of architectural works based on the point of view of the philosophy of science and Islamic law. This research aimed to solve problems related to the infringement of architectural works as copyright through concepts in the philosophy of science and Islamic law. The research method used a philosophical approach and theoretical approach. The results showed that the legal protection of architectural works as copyrighted works from the epistemological point of view was based on the boundaries of science as obtained through experience. Then, it tested empirically to produce science with an objective, rational nature and methods carried out using science from acceptable and reliable researchers so that the results of architectural works by applying elements of culture, science and technology have the quality of works that are not in doubt of their authenticity. In Islamic law, the legal protection of architectural works leads to moral rights owned by the creator because of the principle of maslahah or public interest, which has the same concept as the Utilitarian theory proposed by Jeremy Bentham. Legal protection of architectural works as copyright refers to an epistemological point of view. Islamic law is based on moral rights as one of the inherent rights owned by the creator as the originality of the work that must be protected. In contrast, economic rights are considered an added value of the moral rights owned by the creator.